2017
DOI: 10.3349/ymj.2017.58.6.1101
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-191 Predicts Poor Prognosis and Promotes Proliferation and Invasion in Esophageal Squamous Cell Carcinoma

Abstract: PurposeAccumulating evidence has shown that dysregulation of microRNA-191 (miR-191) is closely associated with tumorigenesis and progression in a wide range of cancers. This study aimed to explore the potential role of miR-191 in esophageal squamous cell carcinoma (ESCC).Materials and MethodsmiR-191 expression was assessed in 93 ESCC tissue specimens by real-time polymerase chain reaction, and survival analysis was performed via Kaplan-Meier and Cox regression analyses. 3-(4,5-dimethyl-2-thiazolyl)-2,5-dipheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…At present, several miRNAs are known to be useful in the early diagnosis of cancers, including miR-21[ 19 ], miR-486[ 20 ], miR-24[ 21 ], and miR-125a-5p[ 22 ]. In addition, miR-191[ 23 ], miR-1908[ 24 ], miR-200c[ 25 ], and miR-217[ 26 ] were found to be potential prognostic indictors in cancer. However, these studies only used a single indictor or a limited number of patients for survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At present, several miRNAs are known to be useful in the early diagnosis of cancers, including miR-21[ 19 ], miR-486[ 20 ], miR-24[ 21 ], and miR-125a-5p[ 22 ]. In addition, miR-191[ 23 ], miR-1908[ 24 ], miR-200c[ 25 ], and miR-217[ 26 ] were found to be potential prognostic indictors in cancer. However, these studies only used a single indictor or a limited number of patients for survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that the silencing of EGR1 reduced cisplatin-induced apoptosis in WHCO1 cells [ 62 ]. Additionally, Gao et al also reported that miR-191 could increase cell proliferation and invasion, which might reduce EGR1 expression by binding its 3′UTR involved in ESCC progression [ 63 ]. SOX2 was the first one identified, located at chromosome 3q26.33, as a 317 amino acid transcription factor containing an HMG domain, which involved in cell proliferation, apoptosis, differentiation and affects the prognosis of ESCC [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…[15] The prognostic value of miR-191 in various cancer types have also been investigated. For example, in the study by Gao et al, [22] Kaplan–Meier and Cox regression analyses demonstrated that overexpression of miR-191 was an independent and significant predictor of esophageal squamous cell carcinoma prognosis. Song et al [23] found that the expression of miR-191 closely associated with the tumor size, pTNM stage, lymph node metastasis and perineural invasion, and poor prognosis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%